Ethics and Animals: Approaches and Theories: Ethics and Animals: Approaches and Theories - Jahed, Mohsen (Bioethics and Health Law Journal (BHL), 2021)
Background and Aim: Moral status of animals has been attended by philosophers such as Pythagoras, Aquinas, Kant, etc. But in the contemporary period, considering this issue both in terms of volume and in quality is not comparable with the previous period. So that the pursuit of philosophical works written in this regard, can also be done with difficulty. This article seeks to introduce the main philosophical mainstream in this area and analyze the philosophical method and introduce the most effective and appropriate for Iran society. Materials and Methods: In this review article, to introduce major approaches and theories in this article is used some of the most important available philosophical and religious texts. This critical review method in this article can be contained following the analytical method (analytic philosophy). Ethical Considerations: In this review article, honesty and integrity have been considered and it has been tried to provide reasonable criteria as the moral duty of the researcher, as far as possible. Findings: The behavior that humans have with animals is the subject of a branch of applied ethics, which is called animal ethics. There are various approaches in animal ethics: an analytical approach, continental approach, pragmatic attitude, and theological approach. On the other hand, the ethics philosophers have used classical theories of ethics in this field and announced their position about animals. In a general classification, these views are in two categories: (1) direct theories (2) indirect theories. The indirect theories include theories of Kant and social contract and direct theories are divided into two categories: ideas and theories believing in the equality of human beings and animals and theories attached to the lack of equality. Conclusion: Although the approaches and theories mentioned above, all can be effective as efficient theoretical tools in support of animal rights and decreasing their suffering, but since Iran is a less philosophical and more religious community, the theological approach can be more efficient in the field of animal rights. *Corresponding Author: Mohsen Jahed; Email: jahed.mohsen@znu.ac.ir; ORCID: https://orcid.org/00000-0002-3953-876X Please cite this article as: Jahed M. Ethics and Animals: Approaches and Theories. Bioeth Health Law J. 2021; 1:1-9: (e5). http://doi.org/10.22037/bhl.v1i1.38130